2015
DOI: 10.2298/sarh1506301v
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among students - a cross-sectional study at three largest universities in Serbia

Abstract: A high percentage of Serbian students consume alcohol, and even though they have their first drink at an early age, they generally drink less than students in many other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Studies have shown a north-to-south gradient of these patterns in Europe (Bryant & Kim, 2012). Southern European countries have a high prevalence of everyday drinking with meals, while northern European countries have a higher prevalence of binge drinking (defined as drinking more than five standard drinks on one occasion (Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014) compared to central European and Mediterranean countries (Kuntsche et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown a north-to-south gradient of these patterns in Europe (Bryant & Kim, 2012). Southern European countries have a high prevalence of everyday drinking with meals, while northern European countries have a higher prevalence of binge drinking (defined as drinking more than five standard drinks on one occasion (Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014) compared to central European and Mediterranean countries (Kuntsche et al, 2015).…”
mentioning
confidence: 99%
“…Another study – the basis of our analysis – examined substance abuse and gambling in the Serbian adult population in the 2014 national survey on lifestyles in Serbia ( Kilibarda, Mravcik, Sieroslawski, Gudelј Rakić, & Martens, 2014 ). Studies on alcohol consumption have also been conducted on adolescent populations ( Golo, Cirić-Janković, Santrić-Milićević, & Simić, 2013 ; The ESPAD Group, 2015 ; Višnjić, Jović, & Grbeša, 2015 ). Data on alcohol consumption among school children have been acquired through the European School Survey Project on Alcohol and Other Drugs, conducted in 2008 and 2011 ( The ESPAD Group, 2015 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glavna prednostna naloga na področju preprečevanja prekomernega pitja alkoholnih pijač po vsej Evropi je zmanjševanje škode zaradi uživanja alkohola med mladimi (Hughes, et al, 2011). Razširjenost nezdravega uživanja alkohola med mladimi se povečuje in je rastoč svetovni pojav v mnogih državah (Višnjić, et al, 2015;Dumbili, 2015).…”
Section: Uvodunclassified
“…In Kenya school going students (13 to 22years), current alcohol use was 34.7% (15), in Ethiopia at the age of 18 to 24 years lifetime alcohol consumption was 30.6% (16). Students who use alcohol had poor academic achievement, absent from class, poor concentration, cannot read their books, criminals and social issues are common (17)(18)(19)(20)(21)(22)(23) Current alcohol user in In United State college students was 68.9% (24), In UK university students was 74% (23), in American college students was 40% ((25), in Brazil university was 83.1 % and 89.3% among having religions and not having religion respectively (26), in Serbia three largest universities was 77.7% (27) and in Thailand school students in the 30days were 14.8% (28). In African countries the finding showed different results.…”
Section: Introductionmentioning
confidence: 99%